Geriatric neuropsychology : practice essentials - Bush, Shane S., 1965-; Martin, Thomas A., 1965- (New York : Psychology Press, 2014)
The text provides a lifespan developmental approach to neuropsychology. It addresses the many issues in neuropsychological assessment that differ between younger and older adults. It describes the symptoms, neuropathology, diagnostic considerations, and treatment options of common neurological disorders associated with aging. It also addresses special considerations related to geriatric neuropsychology, such as ethical issues, family systems issues, decision-making capacity, cultural consideration, and medical/medication/substance use issues. Additionally, a list of resources for the elderly and their families is also provided.
Part I. Introduction Part II. Assessment. Chapter 1. The Clinical Interview Chapter 2. Selection and Use of Screening Measures in Geriatric Neuropsychology Chapter 3. Neuropsychological Batteries for Older Adults Chapter 4. Applications of Technology to Assessment and Intervention with Older Adults Chapter 5. Testing Accomodations in Geriatric Neuropsychology Chapter 6.Cultural Considerations in Neuropsychological Assessment of older adults Chapter 7. Structural and Functional Neuroimaging Findings in Normal and Pathological Aging Part III. Neuropsychological Disorders. Chapter 8. Neuropsychology of Alzheimer's Disease and other Dementias Chapter 9. Cerebrovascular Disorders: Neurocognitive and Neurobehavioral Features Chapter 10. Neuropsychology of Parkinson's Disease and its Dementias Chapter 11. Traumatic Brain Injury and the Older Adults Part IV. Clinical Considerations in Geriatric Neuropsychology. Chapter 12. Co-Occuring Psychiatric and Neurological Impairments in older adults Chapter 13.Sleep Disorders and Geriatric Neuropsychology Chapter 14.Geriatric Pain and Neuropsychological Assessment, Chapter 15. Geriatric Psychopharmacology Chapter 16. Substance Abuse in older adults Chapter 17. Neuropsychologists as Family Service Providers Chapter 18.Decision-Making Capacity in the Impaired older adult Chapter 19.Ethical Issues in Geriatric Neuropsychology.
Originally published: 2005 by Taylor & Francis
This edition published in 2012 by Psychology Press
First issue in paperback
Includes bibliographical references and index.
Keywords: Neuropsychologie -- Ouderen; Geriatric neuropsychiatry